2017
DOI: 10.4088/jcp.15r10197
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Test Performance to Enhance Identification of Subjects at Clinical High Risk for Psychosis and Be Most Promising for Predictive Algorithms for Conversion to Psychosis

Abstract: CHR has mild to moderate globally distributed neuropsychological performance deficits that lie between FEP and HCs. Neuropsychological performance deficits are greater in CHR-P than in CHR-NP, but they overlap, reducing their current utility for risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
60
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 0 publications
12
60
2
Order By: Relevance
“…Not only brain structural alterations but also neurocognitive impairments predate the onset of frank psychosis. Verbal learning and memory are among the most impaired cognitive domains in ARMS (Hauser et al., ; Studerus, Papmeyer, & Riecher‐Rössler, ) as well as FEP patients (Fatouros‐Bergman, Cervenka, Flyckt, Edman, & Farde, ) and may potentially be useful for the early detection and intervention of these disorders (Fusar‐Poli, Deste, et al., ). The California Verbal Learning Test (CVLT) is a test used for the assessment of a wide variety of verbal learning and memory measures and may be applied over a vast area of disorders such as dementia and Alzheimer's disease, traumatic brain injuries, brain lesions, schizophrenia and many more (Delis, Freeland, Kramer, & Kaplan, ; Jacobs & Donders, ).…”
Section: Introductionmentioning
confidence: 99%
“…Not only brain structural alterations but also neurocognitive impairments predate the onset of frank psychosis. Verbal learning and memory are among the most impaired cognitive domains in ARMS (Hauser et al., ; Studerus, Papmeyer, & Riecher‐Rössler, ) as well as FEP patients (Fatouros‐Bergman, Cervenka, Flyckt, Edman, & Farde, ) and may potentially be useful for the early detection and intervention of these disorders (Fusar‐Poli, Deste, et al., ). The California Verbal Learning Test (CVLT) is a test used for the assessment of a wide variety of verbal learning and memory measures and may be applied over a vast area of disorders such as dementia and Alzheimer's disease, traumatic brain injuries, brain lesions, schizophrenia and many more (Delis, Freeland, Kramer, & Kaplan, ; Jacobs & Donders, ).…”
Section: Introductionmentioning
confidence: 99%
“…ARMS patients are exposed to a high risk of developing frank psychosis, with transition risks up to 36% after 3 years of follow-up (Fusar-Poli et al, 2012a). Previous studies showed that not only positive psychotic symptoms such as hallucinations, delusions and thought disorders, but also negative symptoms (Cotter et al, 2014) and cognitive impairments (for meta-analysis see Hauser et al, 2017) are frequently present in ARMS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from positive and negative symptoms, cognitive impairments are regarded as a core feature of psychosis and are present in a considerable number of ARMS and FEP patients (Hauser et al, 2017). Although less severe than in FEP patients, ARMS patients show significant and widespread impairments in different domains of cognitive functioning such as general intelligence, attention/vigilance, verbal learning, visual learning, social cognition, executive functioning, processing speed, verbal fluency, working memory and verbal and visual memory (Fusar-Poli et al, 2012b;Hauser et al, 2017). It has been shown that ARMS patients with later transition to psychosis perform significantly worse in cognitive tasks than patients without later transition in nearly all cognitive domains (Hauser et al, 2017;Riecher-Rössler and Studerus, 2017;Studerus et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The team provides personalized care including case management, psychosocial treatment and medication over 2 years according to the literature (Iyer & Malla, 2014). The patient is referred to another psychiatric service in cases of chronic disease diagnosis such as (Hauser et al, 2017). schizophrenia spectrum disorders or bipolar disorder at the end of the 2 years. Patients without a chronic disorder are informed that they can contact team members in case of symptom exacerbation.…”
Section: Two Years Latermentioning
confidence: 99%